Research of Design of Spindle Transmission System of Peeling Machine for Large Diameter Stainless Steel Bar - Mei Chao Qu Yinhu Qi Zhixu Cheng Xiaole Liu Xiaoni Zhang Xueshuo He Xuan (Jixie chuandong)
Based on Adams software, a multi-rigid-body dynamics model of the spindle transmission system of the peeling machine is established. The key components of the spindle transmission system of the peeler are flexibly processed by ANSYS, and the rigid-flexible coupling model of the spindle transmission system is constructed. The gear engagement process of the spindle transmission system is simulated by simulating the rotating speed of the gears at all levels of the spindle transmission system and setting the contact force parameters of the gears. The transmission ratio of the gears is verified. It is determined that the acceleration fluctuation mainly depends on the excitation frequency. At the same time, the tangential direction of the driving gear-transmission gear and the transmission gear-spindle gear is determined. The simulation values of force and radial force are 3 649.21 N, 1 580.15 N, 3 598.64 N and 1 415.13 N, respectively, which are in good agreement with the theoretical values, and the reliability of the simulation is verified by gear meshing frequency. Finally, 10 nodes with the maximum equivalent stress of three flexible parts in the simulation process are extracted, and the results are lower than the allowable stress of gear material, which can provide theoretical reference for the design and manufacture of the spindle drive system of high-performance peeler in practical application.